2005
DOI: 10.1111/j.1748-5827.2005.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilic dermatitis and immunemediated haematological disorders in a dog: suspected adverse reaction to carprofen

Abstract: This report describes the clinical and pathological findings of a suspected idiosyncratic adverse drug reaction in a young dog. The patient presented with sudden onset, severe skin lesions together with episodes of collapse. Investigations revealed a neutrophilic dermatitis with vasculitis, immune-mediated haemolytic anaemia and thrombocytopenia. Similar pathology has been described in human cases of Sweet's syndrome. The chronology of events suggested an adverse drug reaction to carprofen, although two antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 22 publications
2
85
2
Order By: Relevance
“…Most of these risk factors have been taken from the human literature (Sokol et al 1992(Sokol et al , 1994, and relatively few have been confirmed in dogs. Sulphonamides, cephalosporin, and carprofen have been linked with IMHA (Bloom et al 1988;Trepanier et al 2003;Trepanier 2004;Mellor et al 2005;Lavergne et al 2006). The association of vaccination in one study was not confirmed in two other studies (Duval and Giger 1996;Astrup et al 1998;Carr et al 2002).…”
Section: Diagnostic Testingmentioning
confidence: 84%
“…Most of these risk factors have been taken from the human literature (Sokol et al 1992(Sokol et al , 1994, and relatively few have been confirmed in dogs. Sulphonamides, cephalosporin, and carprofen have been linked with IMHA (Bloom et al 1988;Trepanier et al 2003;Trepanier 2004;Mellor et al 2005;Lavergne et al 2006). The association of vaccination in one study was not confirmed in two other studies (Duval and Giger 1996;Astrup et al 1998;Carr et al 2002).…”
Section: Diagnostic Testingmentioning
confidence: 84%
“…Carprofen hypersensitivity has been suspected as the cause of drug eruption resembling Sweet syndrome in 2 dogs 27 and as a cause of neutrophilic dermatitis and vasculitis in 1 dog. 15 To the authors' knowledge, this is the first reported association between carprofen and TEN. Carprofen belongs to the propionic acid class of nonsteroidal anti-inflammatory drugs (NSAIDs), including ketoprofen, ibuprofen, naproxen, benoxaprofen, and fenoprofen, 6 with which carprofen shares an ATC code up to the fourth level (WHO).…”
Section: Discussionmentioning
confidence: 99%
“…Cats with pain scores above these limits would immediately receive the rescue analgesic drug and be excluded from the study. The presence of any adverse effects, including vomiting, diarrhea, decreased appetite, lethargy, melena, somnolence, hyperactivity, skin reactions, and constipation were recorded [2632]. …”
Section: Methodsmentioning
confidence: 99%